2021
DOI: 10.3390/molecules26123619
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Melanoma-Initiating Cells by Caffeine: In Silico and In Vitro Approaches

Abstract: The beneficial effects of coffee on human diseases are well documented, but the molecular mechanisms of its bioactive compounds on cancer are not completely elucidated. This is likely due to the large heterogeneity of coffee preparations and different coffee-based beverages, but also to the choice of experimental models where proliferation, differentiation and immune responses are differently affected. The aim of the present study was to investigate the effects of one of the most interesting bioactive compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 68 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…Collectively, caffeine treatment affects the expression of pro- and anti-angiogenic and inflammatory factors of the retina and choroid endothelium, which could contribute to the effect of caffeine in mitigating ocular inflammation and angiogenesis. A recent study identified tyrosinase as a major target of caffeine action in modulating the proliferation and expression of various immunomodulatory cytokines and chemokines in melanomas ( Tabolacci et al, 2021 ). The role of choroidal melanocytes in immunomodulation and pathogenesis of nAMD, and their response to caffeine remain a subject of future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, caffeine treatment affects the expression of pro- and anti-angiogenic and inflammatory factors of the retina and choroid endothelium, which could contribute to the effect of caffeine in mitigating ocular inflammation and angiogenesis. A recent study identified tyrosinase as a major target of caffeine action in modulating the proliferation and expression of various immunomodulatory cytokines and chemokines in melanomas ( Tabolacci et al, 2021 ). The role of choroidal melanocytes in immunomodulation and pathogenesis of nAMD, and their response to caffeine remain a subject of future investigation.…”
Section: Discussionmentioning
confidence: 99%
“…One of such strategies comprises GLUT inhibitors, being extensively explored for their antineoplastic potential ( 9 ). Natural products like genistein ( 10 ), quercetin ( 11 ), caffeine ( 12 ), phloretin ( 13 ), resveratrol ( 14 ), curcumin ( 15 ), and small synthetic inhibitors like cytochalasin B ( 16 ), fasentin ( 17 ), WZB117 ( 18 ), thiazolidinedione ( 19 ), STF31 ( 20 ), BAY876 ( 21 ), DRB18 ( 22 ), silybin ( 23 , 24 ), and naringenin ( 25 , 26 ) have been explored for their GLUT-inhibiting potential. They are also in various stages of preclinical and clinical trials ( 27 ).…”
Section: Introductionmentioning
confidence: 99%
“…The research found that caffeine had potent antiproliferative effects on melanoma cells, possibly by promoting melanin production and reducing the secretion of inflammatory signals. Tyrosinase was identified as a key player in mediating caffeine's effects on melanoma, suggesting its importance in these mechanisms [29].…”
Section: Caffeinementioning
confidence: 99%